PRIVACY AND DATA PROTECTION - L. Determann (Московский журнал международного права)
Introduction. This article provides an overview regarding privacy and data protection laws and principles around the world. It is based on lectures by the author on May 17, 2018 at Moscow State Institute of International Relations (MGIMO) and Lomonosov Moscow State University (MSU) on the occasion of the publication of a Russian version of the 3 rd edition of Determann's Field Guide to Data Privacy Law.Materials and methods. Materials include national and international laws and scholarly articles and books relating to privacy and data protection. Methods follow general principles of German and United States legal commentary.Research results. People, societies and governments value and protect privacy quite differently around the world. Consequently, data privacy, data security and data protection laws and policies vary significantly. Particularly pronounced are differences in the approach to the protection of privacy and information freedom and data processing regulation in the United States and the European Union.Discussion and conclusions. Law and policy makers around the world must analyze and balance their people's specific needs for privacy, security, freedom of information, technical progress, economic development and other values and objectives as they decide whether to adopt European Unionstyle data processing regulation, enact specific individual privacy laws as the United States, or pursue alternative approaches. They need to consider the different meanings of individual privacy, data security, information self-determination and data protection, as well as the different functions of data privacy laws, data processing regulation, record retention statutes and data residency requirements.